THE ROLE OF THE PUBLIC PROSECUTORS IN PROVIDING LIFETIME CRIMINAL PROSECUTIONS AGAINST THE CRIMINAL ACTS OF VIOLENT THEFT (STUDY OF GORONTALO PROSECUTORS OFFICE) - Yusrianto Kadir; Roy Moonti; Ririn Lihawa (IHSA Institute, 2022)
According to article 365 paragraph 4 of the Criminal Code, criminal sanctions for life for the defendant are expected to provide a deterrent effect, but on the contrary, based on the facts on the ground, the purpose of implementing this article has not been effective because the crime of theft with violence is still rife. The purpose of writing in this study is to find out the role of the public prosecutor in giving lifelong criminal charges to the perpetrators of the crime of theft accompanied by acts of violence, the study of Gorontalo Prosecutor's Office, and what factors hinder and encourage public prosecutors in providing life imprisonment against perpetrators of the crime of theft with violence. Study of Gorontalo Prosecutor's Office. The type of research used is empirical research which is a legal research method that uses empirical facts taken from human behavior, both verbal behavior obtained from interviews and real behavior through direct observation. The role of the Gorontalo District Attorney in the case of theft with violence can be divided into 3 (three) things, namely the normative role, the ideal role and the factual role, then the obstacles faced were limited to the uncooperative attitude of the defendant, while in substance the implementation of the demands was encountered, namely at the coordination stage. with the leadership within the Gorontalo City Public Prosecutor's Office.